THE PSYCHOLINGUISTIC ANALYSIS OF STUDENT PROBLEMS IN SPEAKING ENGLISH - Ahmad Wahyudi Aras; Radiah Hamid; Andi Bulkis Maghfirah Mannong (FKIP Unismuh Makassar, 2022)
The research aims to ‘The Psycholinguistic Analysis of the Students Problem in Speaking English at Third Semester of Fkip Muhammadiyah Makassar University in the Academic Year Of 2020/2021. In this research, the researcher used the Qualitative research method. The researcher used Purposive Sampling technique to determine the sample. The researcher chose the third semester as sample that consisted of 30 students. In collecting data, the researcher used observation and interview. Based on the result of the research, the researcher found that the psychological problems of the students were fear of making mistakes, lack of confidence, nervous of facing new guy(anxiety), and factors caused the problems were bad pronunciation, low vocabulary, worry of people think, fear of judging. Those result were proved the previous related studies which Fitriani et al (2005), Xinghua (2007) claimed that students’ psychological problems were fear of making, lack of confidence and anxiety, which caused factors were bad pronounce, low in grammar and vocabulary, but they didn’t claimed as same as the researcher found that fear of judging and worry of people think were caused the students’ feeling anxiety and feeling not confidence when they speaking in English.